THE EFFECTIVENESS OF FISHERIES COUNSELING IN THE DEVELOPMENT ON FISH CULTIVATOR GROUPS IN THE DHARMASRAYA DISTRICT OF WEST SUMATRA PROVINCE - Sandrawita Sandrawita; Kusai Kusai; Hazmi Arief (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe purpose of this research was to know descriptively about the Effectiveness of Fisheries Extension Workers in the development of a group of fish farmers in Dharmasraya Regency, West Sumatra Province. Knowing the constraints of Fisheries Instructors in the field in the activities and implementation of efforts to develop a group of fish farmers in Dharmasraya Regency, West Sumatra Province. This research was carried out in November 2018 in Dharmasraya Regency, West Sumatra Province. The method used in this study was a survey method (survey).The effectiveness of the instructor in the development of the group of fish farmers in the Dharmasraya district, were categorized quite effective in carrying out their duties as motivators, educators, communicators, organizers, consultants, and catalysts. The effectiveness of instructors was categorized into beginners, intermediate classes, and advanced classes. The effectiveness of counseling classes for beginner fish cultivator groups obtained a score of 414 with the category quite effective. The middle category fish cultivator group obtained a score of 494 with the category quite effective. While the advanced fish cultivator group obtained a score of 731 with the category quite effective. Of the three extension workers, both are classified as quite effective. To measure the effectiveness of the performance of fisheries instructors in Dharmasraya Regency, human resource performance measurements were carried out using the Key Performance Indicator (KPI) analysis. The effectiveness of fisheries instructors in the Dharmasraya district calculated based on the performance of human resources is quite effective with the acquisition of a final score of 48.Keywords:Effectiveness of counseling, Fish cultivator group